Coach strategies for addressing psychosocial challenges during the return to sport from injury - Podlog, L.; Dionigi, R. (Journal of Sports Sciences, 2010)
The purpose of this study was to examine coach strategies for addressing athletes' psychosocial challenges in returning to sport following injury rehabilitation. Qualitative interviews with eight elite coaches from the Western Australian Institute of Sport (WAIS) in Perth, Australia revealed that coaches facilitated athletes' return to sport from injury through a variety of means, but did not typically provide systematic forms of assistance. Coaches commented that the idiosyncratic nature of the injury experience meant that they needed to apply strategies consistent with athletes' particular psychosocial needs. Such strategies included: (a) coordination of a "team approach" to rehabilitation; (b) fostering open communication with athletes and treatment team members; (c) social support; (d) positive thinking and goal setting; and (e) role models. Analysis of these strategies revealed that coaches attempted to address competence, autonomy, and relatedness needs in facilitating athletes' return from injury. These findings suggest that self-determination theory may be a valuable approach for examining coach forms of assistance regarding athletes' return to competition following injury. Findings are discussed in relation to injury literature and self-determination theory. Suggestions for future research are also presented.